DAMPAK PEMBANGUNAN PANTAI UTARA JAKARTA TERHADAP KEGIATAN PERIKANAN : STUDI KASUS DI KECAMATAN PADEMANGAN, JAKARTA UTARA - Supartono Supartono; John Haluan; M. Fedi A. Sondita; Manuwoto Manuwoto (Buletin PSP, 2007)
The course of development in Jakarta Coast (Pademangan Sub-District) bears critical impact on fishery activities, i.e. degradation of coastal and marine environment. This research was conducted to identify the extent of such degradation attributed to the coastal development, particularly coastal reclamation. Data on the actual condition of Jakarta North coast were collected by conducting rapid rural appraisal (RRA), i.e., interviews with respondents (fishermen, community leader, local officials) and field survey. Hydro-oceanographic data is obtained through marine survey in collaboration with Oceanography Office of Indonesia Marine Force for a 2-week period (from July 15th until July 29th, 2004) and secondary data from LIPI (Indonesian Institute of Science) and Fishery Office and Regional Development Planning Agency of North Jakarta Municipality, sub-district as well as village administration in Pademangan. Data analysis and processing were carried out through Geographic Information System (SIG) of Information System Engineering to process, organize, store, manipulate and present spatial data for various types of applications. This study shows that the sea surface temperature, salinity, dissolved chemicals have exceeded their threshold levels and plankton and hydro-oceanographic data have significantly changed; such changes hindered fishery activities. However, several fishery activities can be maintained and improved, such as fish processing. Fishing activities can be sustained in certain areas in the bay while promoting marine environment quality that promotes marine sports/recreations.